Intractable Pneumothorax Treated With Endobronchial Watanabe Spigots. Issue 4 (October 2016) - Okui, Masayuki; Kohno, Mitsutomo; Hasegawa, Naoki; Kamiyama, Ikuo; Ohtsuka, Takashi
Abstract : Pneumothorax secondary to nontuberculous mycobacterial lung disease is often intractable and associated with high mortality. An endobronchial Watanabe spigot (EWS) is a silicon plug developed for bronchoscopic bronchial occlusion. Here we report a case of intractable pneumothorax secondary to nontuberculous mycobacterial lung disease successfully treated using EWSs. Occlusion of the multiple ectatic bronchi connected to the bronchopleural fistula was essential for optimal effect of the EWSs.